2019
DOI: 10.1139/cjpp-2019-0188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol postconditioning on cerebral ischemia in mice: role of the sirtuin-1 pathway

Abstract: Evidence has demonstrated that resveratrol preconditioning exhibits neuroprotection against cerebral ischemia–reperfusion (IR) injury. The current investigation aimed to explore whether pharmacological postconditioning, by administering resveratrol, after a sustained ischemia and prior to prolonged reperfusion abrogates cerebral IR injury. Cerebral IR-induced injury mice model was employed in this study to evaluate the neuroprotective effects of pharmacological postconditioning with resveratrol (30 mg/kg; i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Among them, 86 records were excluded due to review, abstracts without full text, not having purified resveratrol, no in vivo experiment, not reporting the number of animals in groups, and or no adequate outcomes (infarction volume or functional outcome determined by neurobehavioral score measured on any scale/rotarod test). Therefore, 54 studies ( Huang et al, 2001 ; Sinha et al, 2002 ; Inoue, 2003 ; Gao et al, 2006 ; Tsai et al, 2007 ; Dong et al, 2008 ; Yousuf et al, 2009 ; Li et al, 2010 ; Sakata et al, 2010 ; Shin et al, 2010 ; Ren et al, 2011 ; Li et al, 2012 ; Shin et al, 2012 ; Hurtado et al, 2013 ; Lanzillotta et al, 2013 ; Lin et al, 2013 ; Orsu et al, 2013 ; Yan et al, 2013 ; Saleh et al, 2014 ; Wang et al, 2014 ; Fang et al, 2015 ; Hermann et al, 2015 ; Ishrat et al, 2015 ; Koronowski et al, 2015 ; Li et al, 2015 ; Narayanan et al, 2015 ; Pandey et al, 2015 ; Pang et al, 2015 ; Abdel-Aleem et al, 2016 ; Jeong et al, 2016 ; Li et al, 2016 ; Lopez et al, 2016 ; Su et al, 2016 ; Wan et al, 2016 ; Yang et al, 2016 ; Al Dera, 2017 ; He et al, 2017 ; Koronowski et al, 2017 ; Yu et al, 2017 ; Faggi et al, 2018 ; Hou et al, 2018 ; Liu et al, 2018 ; Dou et al, 2019 ; Grewal et al, 2019 ; Park et al, 2019 ; Yan et al, 2019 ; Alquisiras-Burgos et al, 2020 ; Lu et al, 2020 ; Mota et al, 2020 ; Pineda-Ramírez et al, 2020 ; Teertam et al, 2020 ; Yao et al, 2020 ; McDonald...…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 86 records were excluded due to review, abstracts without full text, not having purified resveratrol, no in vivo experiment, not reporting the number of animals in groups, and or no adequate outcomes (infarction volume or functional outcome determined by neurobehavioral score measured on any scale/rotarod test). Therefore, 54 studies ( Huang et al, 2001 ; Sinha et al, 2002 ; Inoue, 2003 ; Gao et al, 2006 ; Tsai et al, 2007 ; Dong et al, 2008 ; Yousuf et al, 2009 ; Li et al, 2010 ; Sakata et al, 2010 ; Shin et al, 2010 ; Ren et al, 2011 ; Li et al, 2012 ; Shin et al, 2012 ; Hurtado et al, 2013 ; Lanzillotta et al, 2013 ; Lin et al, 2013 ; Orsu et al, 2013 ; Yan et al, 2013 ; Saleh et al, 2014 ; Wang et al, 2014 ; Fang et al, 2015 ; Hermann et al, 2015 ; Ishrat et al, 2015 ; Koronowski et al, 2015 ; Li et al, 2015 ; Narayanan et al, 2015 ; Pandey et al, 2015 ; Pang et al, 2015 ; Abdel-Aleem et al, 2016 ; Jeong et al, 2016 ; Li et al, 2016 ; Lopez et al, 2016 ; Su et al, 2016 ; Wan et al, 2016 ; Yang et al, 2016 ; Al Dera, 2017 ; He et al, 2017 ; Koronowski et al, 2017 ; Yu et al, 2017 ; Faggi et al, 2018 ; Hou et al, 2018 ; Liu et al, 2018 ; Dou et al, 2019 ; Grewal et al, 2019 ; Park et al, 2019 ; Yan et al, 2019 ; Alquisiras-Burgos et al, 2020 ; Lu et al, 2020 ; Mota et al, 2020 ; Pineda-Ramírez et al, 2020 ; Teertam et al, 2020 ; Yao et al, 2020 ; McDonald...…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of the mutant HD protein, the SIRT1-TORC1 interaction was inhibited, repressing BDNF transcription [155]. In addition to providing neuroprotection against neurodegenerative diseases, the activation of SIRT1 has been shown to confer protection against cerebral ischemia [156] and metabolic diseases such as obesity [157] and type 2 diabetes [158].…”
Section: Discussionmentioning
confidence: 99%
“…However, more research is needed to develop pathophysiological links. Neuronal α-synuclein expressions in the peripheral nervous system block viral CNS invasion and replication of RNA viruses in the nervous system (Grewal et al, 2019 ). In a preclinical study, α-synuclein knockout mice showed B and T cell deficiencies.…”
Section: Covid-19 and Parkinson’s Diseasementioning
confidence: 99%